Storytelling in northern Zambia theory, method, practice and other necessary fictions - Cancel, Robert; Cambridge University Museum of Archaeology and Anthropology. World Oral Literature Project; Open Book Publishers (Open Book Publishers, 2013)
"Storytelling plays an important part in the vibrant cultural life of Zambia and in many other communities across Africa. This innovative book provides a collection and analysis of oral narrative traditions as practiced by five Bemba-speaking ethnic groups in Zambia. The integration of newly digitalised audio and video recordings into the text enables the reader to encounter the storytellers themselves and hear their narratives as they were recounted during Robert Cancel's research trips to Zambia. Robert Cancel's thorough critical interpretation, combined with these newly digitalised audio and video materials, makes Storytelling in Northern Zambia a much needed addition to the slender corpus of African folklore studies that deal with storytelling performance. Cancel threads his way between the complex demands of African fieldwork studies, folklore theory, narrative modes, reflexive description and simple documentation and succeeds in bringing to the reader a set of performers and their performances that are vivid, varied and instructive. He illustrates this living narrative tradition with a wide range of examples, and highlights the social status of narrators and the complex local identities that are at play. Cancel's innovative study tells us not only about storytelling but sheds light on the study of oral literatures throughout Africa and beyond. Its innovative format, meanwhile, explores new directions in the integration of primary source material into scholarly texts. This book is part of our World Oral Literature Series in conjunction with the World Oral Literature Project."--Publisher's website.
Audio-Visual Resources -- Acknowledgements -- Foreword by Mark Turin -- I. Writing Oral Narrative: The Role and Description of Self in Recording Living Traditions -- II. The Tabwa Context: Mature Shifting of Frames and Adolescent Assertion -- III. Chiefs, Tricksters and Christians: Bemba Tales and Lessons -- IV. Bisa Storytelling: The Politics of Hunting, Beer-Drinks, and Elvis -- V. Telling Tales While Keeping Secrets: Two Lunda Storytelling Sessions -- VI. Stories on Demand: A Performance Session Among the Bwile -- VII. Conclusion: Lessons from Frozen Moments -- Works cited -- Index.
Available through Open Book Publishers.
Includes bibliography (pages 261-270) and index.
Digitized audio and video recordings of the narratives and the storytellers are integrated into the text. Additional links are available from the publisher's website.
Mode of access: World Wide Web.
Keywords: Bemba (African people) -- Folklore; Bisa (Zambian people) -- Folklore; Bwile (African people) -- Folklore; Folklore -- Zamia; Oral tradition -- Zambia; Southern Lunda (African people) -- Folklore; Tabwa (African people) -- Folklore; Tales -- Zambia